2011
DOI: 10.1051/0004-6361/201116841
|View full text |Cite
|
Sign up to set email alerts
|

The escape of ionising radiation from high-redshift dwarf galaxies

Abstract: Context. The UV escape fraction from high-redshift galaxies plays a key role in models of cosmic reionisation. Because it is currently not possible to deduce the escape fractions during the epoch of reionisation from observations, we have to rely on numerical simulations. Aims. We aim to better constrain the escape fraction from high-redshift dwarf galaxies, as these are the most likely sources responsible for reionising the Universe. Methods. We employ a N-body/SPH method that includes realistic prescriptions… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
67
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 86 publications
8
67
1
Order By: Relevance
“…Previous studies have shown the importance of the porosity of the inter-stellar medium for the escape fraction (Ciardi et al 2002;Fernandez & Shull 2011), especially in the vicinity of the sources (Paardekooper et al 2011). Our results refine the study of Kimm & Cen (2014), who found that in galaxies of low escape fraction the optical depth in a radius of 100 pc is ∼ 2 − 4, large enough to absorb the majority of produced ionizing photons.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Previous studies have shown the importance of the porosity of the inter-stellar medium for the escape fraction (Ciardi et al 2002;Fernandez & Shull 2011), especially in the vicinity of the sources (Paardekooper et al 2011). Our results refine the study of Kimm & Cen (2014), who found that in galaxies of low escape fraction the optical depth in a radius of 100 pc is ∼ 2 − 4, large enough to absorb the majority of produced ionizing photons.…”
Section: Discussionsupporting
confidence: 87%
“…However, high resolution is essential for the computation of the escape fraction, since the main constraint on the escape fraction is the local environment of the sources (Paardekooper et al 2011). Furthermore, this high resolution is necessary to resolve star formation in the abundant low-mass proto-galaxies that are likely the main drivers of reionization (Paper I, Wise et al 2014).…”
Section: Computation Of the Escape Fraction Of Ionizing Photons From mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the value of f esc for an individual galaxy is strongly dependent on its chemical, structural, and kinematic properties, and there exists considerable theoretical and observational evidence to suggest that the average f esc does indeed vary with redshift, mass, and/or star formation rate (e.g. Gnedin et al 2008;Wise & Cen 2009;Paardekooper et al 2011;Yajima et al 2011;Kuhlen & Faucher-Giguère 2012;Mitra et al 2013;Paardekooper et al 2015). …”
Section: An Evolving Escape Fractionmentioning
confidence: 99%
“…However, SNe may also open low-density channels in the ISM, e.g. by expelling gas in winds, through which ionizing photons may escape more easily (e.g., Dove, Shull, & Ferrara 2000;Fujita et al 2003;Wise & Cen 2009;Paardekooper et al 2011). This makes it easier for galaxies to reionize the Universe.…”
Section: Impact On Reionizationmentioning
confidence: 99%